História Oral de Vida de professores de escolas ribeirinhas da Amazônia - Cruz, Daiane Rodrigues da (Brasil, 2025)
This study addresses the need to value the life stories of riverside teachers, as they bring significant experiences and practices essential for developing pedagogical strategies that enhance the teaching-learning process. The objective was to understand the oral life histories of teachers from riverside schools in the Mamurú region, located at the border between the municipalities of Parintins (AM) and Juruti (PA), and to contribute to reflections on Rural Education. The methodological approach was based on a historical perspective, employing oral history research, including thematic interviews with four teachers, which were recorded and transcribed. Theoretical contributions came from Freire (1996), Delgado (2010), Hage (2011), Parente (2014), Arroyo, Caldart, and Molina (2011). The results highlighted challenges such as the distance to schools, lack of infrastructure and teaching materials, absence of continuous training, and difficulties caused by the border between Juruti and Parintins. However, the study also identified the potential of working with multigrade classes through multidisciplinary and creative approaches, considering the children's realities. It emphasized the importance of the relationship between schools and riverside communities.